Trypanocidal activity of a thioacyl-thiosemicarbazide derivative associating both immunostimulating thalidomide and anti-parasitic thiosemicarbazide pharmacophores - Kasséhin, Urbain C.; Gbaguidi, A. Fernand; McCurdy, Christopher R.; Poupaert, Jacques H. (My University, 2015)
African trypanosomiasis remains a life-threatening disease and there is nowadays an urgent need for improved therapeutic agents for this pathology. In this context, in order to create novel anti-protozoa prototype containing both a trypanocidal thiosemicarbazide moiety and an immuno-potentiating thalidomide-like, a hybrid structure was designed on the basis of a convergent synthesis process, synthesized and assayed for its potential trypanocidal activity. Initial biological results are very promising. The structure of the target compound was ascertained on the basis of 13C-NMR, IR spectroscopy and semi-empirical AM1/PM3 quantum-mechanical calculations
Keywords: Trypanocidal activity; immunostimulating thalidomide; thioacyl-thiosemicarbazide; thiosemicarbazide pharmacophore; Schotten-Baumann thioacylation reaction.